Three rare-earth incorporating 6-peroxotantalo-4-selenates and catalytic activities for imidation reaction. Issue 26 (9th June 2022) - Du, Weixin; Liu, Yufeng; Sun, Junjun; Wang, Haiying; Yang, Guoping; Zhang, Dongdi
Abstract : Herein we present three new selenotantalate-based lanthanide derivatives with good catalytic activities for imidation reactions. Abstract : Functionalization with belt lanthanide groups allows for the crystallization and structural characterization of homometallic selenotantalates, CsK[Ln(H2 O)6 Se4 (TaO2 )6 (OH)3 O18 ]· n H2 O (Ln = Eu/Gd, n = 14 (STD-Eu, STD-Gd ) and Ln = Lu, n = 12 (STD-Lu )). The basket-shaped {Se4 (TaO2 )6 } archetype is assembled in a simple one-pot reaction of Na2 SeO3 and K8 [Ta6 O19 ]·17H2 O in acidic aqueous medium (pH 2) and in the presence of hydrogen peroxide. This unit has been proven to be an effective precursor for the preparation of a range of new POMs containing the {Se4 (TaO2 )6 } unit. The lanthanide derivatives STD-Eu, STD-Gd and STD-Lu have been fully characterized with single-crystal X-ray diffraction, IR spectroscopy, TG analysis and PXRD in the solid state. The photoluminescence and lifetime decay behaviours of STD-Eu have been studied at room temperature, and the photoluminescence spectrum displays the characteristic emission of the Eu 3+ cation. In addition, the catalytic activities of STD-Eu, STD-Gd and STD-Lu on the reaction of phthalic anhydride with phenylamines have been investigated. STD-Eu shows good catalytic activities for imidation reactions.